Application of Solar Cell on Organic Waste Shredding Machine for Compost Fertilizer Production Especially Manure from Pig Farms: A Case Study in Sustainable Energy Development - Liga, Marthen; Sampe, Aris; Lefaan, Yosef; Oktaviani, Theresia Wuri; Khaliq, Idham (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2024)
Organic waste management in Indonesia faces significant challenges due to the high greenhouse gas emissions produced. In 2020, greenhouse gas emissions from waste management in Indonesia especially the waste sector contributes around 3.2% of total global emissions. The use of organic waste shredders is one solution to minimize waste volume; althought still heavily rely on conventional energy, which is not environmentally friendly. This study aims to evaluate the implementation of solar photovoltaic (PV) technology in organic waste shredding machines to enhance energy efficiency and reduce environmental impacts. An experimental approach was used in this research. Data were collected through measurements of energy generated by the solar cells, energy consumed by the machine, and the organic waste shredding output processed into compost fertilizer. The results showed that use of solar cells could generate an average of 5.8 kWh of energy per day, with machine energy efficiency reaching 72%. Compared to conventional energy, the use of solar cells increased the shredder machine's productivity to 25 kg/hour and reduced greenhouse gas emissions by up to 70%. Additionally, machine operating time increased by 20% compared to machines using conventional energy.  This increase is due to the solar cell technology itself. In conclusion, application of solar cell technology in organic waste shredders not only improves operational efficiency but also significantly contributes to carbon emission reduction. The research  contribution is to offer concrete solutions that support the achievement of national and global carbon emission reduction targets, as well as creating a waste management model that can be applied in various regions in Indonesia and the world.